Review: Analisis Kandungan Vitamin C Pada Pangan Dengan Metode Kuantitatif - Lilik Febriyani; Ika Elvina Rahmawati; Dinah Suwaybatul Aslamiyah; Firdha Senja Maelaningsih (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Vitamin C is a nutritious substance that can eliminate all free radicals that can kill tissue cells in the body. The water-soluble vitamin C is commonly found in citrus fruits, red dragon fruit, pineapple, paprika and cayenne pepper. Based on the results of a review of the journals used in 2013-2023. The purpose of this review article is to determine the vitamin C content in food using several methods, one of which is the Iodimetry, Spectrophotometry and High Performance Liquid Chromatography (HPLC) methods. The highest levels of vitamin C were by the UV-Vis spectrophotometry method on pineapple fruit samples and by the iodimetry method on red dragon fruit samples.